Detection of Microbial 16S rRNA Gene in the Blood of Patients With Parkinson’s Disease - Qian, Yiwei; Yang, Xiaodong; Xu, Shaoqing; Wu, Chunyan; Qin, Nan; Chen, Sheng-Di; Xiao, Qin (Frontiers in Aging Neuroscience, 2018)
Emerging evidence suggests that the microbiota present in feces plays a role in Parkinson’s disease (PD). However, the alterations of the microbiome in the blood of PD patients remain unknown. To test this hypothesis, we conducted this case-control study to explore the microbiota compositions in the blood of Chinese PD patients. Microbiota communities in the blood of 45 patients and their healthy spouses were investigated using high-throughput Illumina HiSeq sequencing targeting the V3-V4 region of 16S ribosomal RNA (rRNA) gene. The relationships between the microbiota in the blood and PD clinical characteristics were analyzed. No difference was detected in the structure and richness between PD patients and healthy controls. The following genera were enriched in the blood of PD patients: Isoptericola, Cloacibacterium, Enhydrobacter, and Microbacterium; whereas genus Limnobacter was enriched in the healthy controls after adjusting for age, gender, body mass index (BMI), and constipation. Additionally, the findings regarding these genera were validated in another independent group of 58 PD patients and 57 healthy controls using real-time PCR targeting genus-specific 16S rRNA genes. Furthermore, not only the genera Cloacibacterium and Isoptericola (which were identified as enriched in PD patients) but also the genera Paludibacter and Saccharofermentans were positively associated with disease duration. Some specific genera in the blood were related to mood disorders. We believe this is the first report to provide direct evidence to support the hypothesis that the identified microbiota in the blood are associated with PD. Additionally, some microbiota in the blood are closely associated with the clinical characteristics of PD. Elucidating these differences in blood microbiomes will provide a foundation to improve our understanding of the role of microbiota in the pathogenesis of PD.